ANTIHYPERGLYCEMIC ACTIVITY TEST OF TEAK LEAVES (Tectona grandis L.) ETHANOL EXTRACT IN STREPTOZOTOCIN-INDUCED RATS - Nuralifah Nuralifah; Parawansah Parawansah; Nurul Febrina Rahmawati (Jurnal Farmasi Sains dan Praktis, 2021)
Diabetes Mellitus is a metabolic disease characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. This study aimed to determine the antihyperglycemic activity of ethanol extract of teak (Tectona grandis L.) leaves in streptozotocin-induced rats. A total of 24 rats were grouped into 6 groups, normal control (Kn), positive control (K+), negative control (K-), and the three groups of teak leaf ethanol extract doses of 100, 200, and 300 mg/kg BW (K1, K2, respectively). and K3), mice were treated for 7 days. Before being given treatment, the rats were first induced using streptozotocin at a dose of 40 mg/kg BW. The results showed the administration of ethanol extract of teak (Tectona grandis L) leaves. doses of 100, 200, and 300 mg/kg BW with the positive control (K+) had significant antihyperglycemic activity in male Wistar strain rats based on the Oneway ANOVA test and post hoc LSD test.